Streaming analytics : concepts, architectures, platforms, use cases and applications - Raj, Pethuru; Surianarayanan, Chellammal; Seerangan, Koteeswaran; Ghinea, George (IET computing series, 2022)
In this book, the authors articulate the challenges associated with streaming data and analytics, describe data analytics algorithms and approaches, present edge and fog computing concepts and technologies and show how streaming analytics can be accomplished in edge device clouds. They also delineate several industry use cases.